The whole is greater than the sum of the parts: piecing together microbial methylated amine metabolism - Borton, Mikayla A., author; Wrighton, Kelly C., advisor; Wilkins, Michael J., committee member; Borch, Thomas, committee member; Chan, Siu Hung Joshua, committee member (Colorado State University. Libraries, 2020)
To view the abstract, please see the full text of the document.
Zip file contains data spreadsheets.
Keywords: hydraulic fracturing; methanogenesis; trimethylamine; metagenomics; gut microbiome; methylated amine metabolism